Unrelated CD3/CD19-Depleted Peripheral Stem Cell Transplantation for Hurler Syndrome. (1st November 2014) - Schwinger, Wolfgang; Sovinz, Petra; Benesch, Martin; Lackner, Herwig; Seidel, Markus; Strenger, Volker; Sperl, Daniela; Raicht, Andrea; Brunner-Krainz, Michaela; Paschke, Eduard; Plecko, Barbara; Urban, Christian
<x xml:space="preserve">Abstract</x> For patients with mucopolysaccharidosis type IH (MPS1-H; Hurler syndrome), early allogeneic hematopoietic stem cell transplantation (HSCT) is the treatment of choice. One boy and one girl aged 20.5 and 22 months, respectively, with MPS1-H received a conditioning regimen consisting of thiotepa, fludarabine, treosulfan, and ATG. Grafts were peripheral blood stem cells from unrelated donors (10/12 and 11/11 matched), that were manipulated by CD3/CD19 depletion and contained 20.3 and 28.2 × 106 CD34+ cells/kg body weight, respectively. Both patients achieved stable hematopoietic engraftment and stable donor chimerism. Neither acute or chronic graft-versus-host disease (GVHD) nor other severe transplant-related complications occurred. At a follow-up of 48 and 37 months, both patients are alive and well with normal levels of α-L-iduronidase and have made major neurodevelopmental progress. Treosulfan-based conditioning offers the advantage of reduced toxicity; the use of unrelated CD3/CD19-depleted peripheral stem cell grafts allows transfusion of high CD34+ cell numbers together with a "tailored" number of CD3+ cells as well as engraftment facilitating cells in order to achieve rapid hematopoietic engraftment while reducing the risk of graft rejection and GVHD. This regimen might be an additional option when unrelated donor HSCT is considered for a patient with MPS1-H.